Testing the buffering hypothesis: Breastfeeding problems, cessation, and social support in the UK. Issue 2 (30th May 2021) - Page, Abigail E.; Emmott, Emily H.; Myers, Sarah
Abstract: Objectives: Physical breastfeeding problems can lead women to terminate breastfeeding earlier than planned. In high‐income countries such as the UK, breastfeeding problems have been attributed to the cultural and individual "inexperience" of breastfeeding, ultimately leading to lower breastfeeding rates. Yet, cross‐cultural evidence suggests breastfeeding problems still occur in contexts where breastfeeding is common, prolonged, and seen publicly. This suggests breastfeeding problems are not unusual and do not necessarily lead to breastfeeding cessation. As humans evolved to raise children cooperatively, what matters for breastfeeding continuation may be the availability of social support during the postnatal period. Here, we test the hypothesis that social support buffers mothers from the negative impact breastfeeding problems have on duration. Methods: We run Cox models on a sample of 565 UK mothers who completed a retrospective online survey about infant feeding and social support in 2017–2018. Results: Breastfeeding problems were important predictors of cessation; however, the direction of the effect was dependent on the problem type and type of support from a range of supporters. Helpful support for discomfort issues (blocked ducts, too much milk) was significantly associated with reduced hazards of cessation, as predicted. However, helpful support for reported milk insufficiency was assoicated with an increased hazard of cessation. Conclusions: Experiencing breastfeeding problems is the norm, but its impact may be mitigated via social support. Working from an interdisciplinary approach, our results highlight that a wide range of supporters who provide different types of support have potential to influence maternal breastfeeding experience.